Mediacja i tłumaczenie w uczeniu się / nauczaniu języków – podobieństwa i różnice - Janowska, Iwona (Neofilolog, 2024)
In the didactics of languages and cultures, mediation often enters into a relationship with translation. After the publication of the Common European Framework of Reference for Languages in 2001, mediation was mainly associated with linguistic transcoding and equated with translation. In the CEFR – Companion volume (2020), the understanding of mediation has been considerably broadened, taking into account the multilingual and multicultural perspective of language use and the conditions for interaction between people with different lifestyles and views. The aim of the paper is to reflect in depth on the nature of the concepts of ‘mediation’ and ‘translation’. Both are interdisciplinary in nature and their main vehicle is language. But there are also many differences between them which do not allow the terms to be used interchangeably. In an analysis of a comparative nature, we will try to show the most important determinants of the mediation and translation process, referring to their use in the context of language learning and teaching.